IMPLEMENTASI LITERASI DIGITAL DALAM MERANCANG DESAIN PEMBELAJARAN MENGGUNAKAN APLIKASI CANVA - Winda Widyaningrum; Endang Sondari (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
One of the challenges of learning in the digital era is being skilled in designing digital technology-based learning media. Canva is an online-based application that provides attractive designs in the form of templates, features, and categories given in it to support creativity for its users. This article describes the function of the Canva application as a learning medium that can be used for educators and students. The purpose of the assessment of Canva's audio-visual learning media is to find out more about the features in the Canva application that can be used to create learning media, with the hope of increasing teacher innovation in designing interesting, effective and interactive learning media so that the planned learning targets are achieved. The research method is by using qualitative research methods, where this method is descriptive development and tends to use analysis. Keywords :digital literacy, learning method, Canva application